Creación de un producto turístico vivencial para el fomento del agroturismo en la comunidad de Agua Fría, cantón Junín - Albán Mero, Angely Brenda (2022)
The purpose of this research was to create an experiential tourism product for the promotion of agrotourism in the Agua Fría community; It is descriptive because a comprehensive analysis of the territory was carried out based on field observation where it was possible to identify farms with tourist potential, the approach is qualitative based on data collection. The methodological process consisted of 3 phases in the first instance it was the general and tourist characterization that was complemented with the situational diagnosis of the study area, through the potentiality sheet, 7 farms with greater potential were identified, and 5 with emerging potential that was obtained through tools such as bibliographic review, fieldwork, community characterization file, potentialities file, SWOT matrix; Phase II corresponded to the analysis of the demand where the perception of the tourist towards the development of tourism products was known, emphasizing that if they would be interested in consuming tourism products linked to agrotourism, it was possible to identify that the main competitors are Portoviejo and Bolívar due to the similar characteristics that they present. In the last phase, an experiential tourism product was structured through the line of an experiential route "Discovering Cold Water land of currincho" where 3 main products were stipulated that are: discovering rural life, ecotourism, nature and fun, These products combine different activities related to agricultural activities, nature, and interaction with the customs and traditions of the town.